Corporate Governance And The Re-Emergence Of A Director’s Duty In Negligence In Malaysia - Hari Chand, Anil Joshi a/l (Journal of Malaysian and Comparative Law, 2019)
A director's duty in negligence in the past did not receive much attention from practitioners of the law as well as from academics primarily beceause the law pertaining to this aspect of a director's duty is tax in comparison with a director's fiduciary duties.